An exergy-based analysis of the effects of public incentives on the so-called “energy efficiency” of the residential sector, with emphasis on primary resource use and economics of scale - Biondi, Alfonso; Caponi, Piermaria; Cecere, Carlo; Sciubba, Enrico (Frontiers in Sustainability, 2024)
Improving building efficiency is essential for reducing energy consumption, greenhouse gas emissions, and operational costs. In OECD Countries the average share of the Residential and Commercial Sector for space conditioning accounts for 30–37% of the cumulative final energy use. The current situation is somewhat typical of post-industrialized Countries: while the technology for reducing the external thermal losses and for installing more energy-conscious devices and procedures (including real-time monitoring and better design of the enclosures) is readily available, the cost of such measures is often perceived as excessive for the private user. For this reason, some governments have resolved to launch incentivization campaigns to encourage both private and public actors to invest in building efficiency. This strategy has been successful and its large-scale application -even if enacted on a preliminary basis- led to substantial reductions of the energy load per square meter −50 to 100 kWh/(m2yr)- so that subsidies and incentives are likely to assume a major role in shaping the energy conversion market. Technologies that are deemed “more environmental benign” or “of strategic interest” will receive institutional funding to promote their implementation, the funds being allocated both to design techniques, new materials and less energivorous devices. Since the funding is usually provided in the form of tax rebates, this approach is not devoid of problems: in fact, previous campaigns at regional and national level in the primary Energy Conversion and in the Transportation Sector have resulted in monumental failures. While it is clearly in the interest of a community to enact a reduction of their final energy uses, it is also true that such incentivization plans, if not properly and carefully implemented, may constitute an economic and ecological “doping” of the market (detail price increases, material and components shortages, etc.). This paper is a follow-up of a previous study conducted in 2021–22 that proposed a rational and thermodynamic-based approach to the issue: in that paper we presented an innovative cost/benefit procedure that considers the primary exergy savings of an “energy saving” intervention and the installation/operation costs and combines them with the statistically foreseeable savings in the improvement of the building seismic class. The method is intended to serve as a possible model for future policy decisions, and it makes use of the fundamental principles of Exergy Analysis augmented by a conventional cost/benefit analysis and by basic resilience considerations. The case study analyzed in the previous paper is re-examined here in the light of some recent normative developments the Eco-Sisma-Bonus (“Superbonus”), the incentivization plan launched between 2014 and 2020 by the Italian Government.